Keterlibatan Negara dalam Mengawal Kebebasan Beragama/ Berkeyakinan (Komentar Akademik atas Judicial Review UU No.1/PNPS/1965) - Tobroni, Faiq (Jurnal Konstitusi, 2010)
A theory having been known in the discourse of civil and political rights is a state has to act by omission (by not to do anything that can limit to as well as oppress these rights). It is this theory that was used as argument to petition for judicial review of law No.1/PNPS/Th.1965. This law was regarded having limited freedom of conscience and religion, that are parts of civil and political    rights.After the implementation of freedom of conscience and religion have been evaluated, this should not be absolute because it will cause instability of harmony of religious community. The uncontrolled freedom, in fact, will encourage the deviation. The deviation that often happens is the mistaken interpretation.It caused the misuse or desecretion of religion.The state as organizer of people life, therefore, has the responsibility  for controling the implementation of religious freedom in the light of harmony, and for preventing it from the misuse or desecretion. It is in  this moment that Law No.1/PNPS/Th.1965 has been regulated to control the religious freedom in the light of harmony.